Ammonia Decomposition in the Process Chain for a Renewable Hydrogen Supply. Issue 10 (22nd July 2022) - Ristig, Simon; Poschmann, Michael; Folke, Jan; Gómez‐Cápiro, Oscar; Chen, Zongkun; Sanchez‐Bastardo, Nuria; Schlögl, Robert; Heumann, Saskia; Ruland, Holger
Abstract: This review article deals with the challenge to identify catalyst materials from literature studies for the ammonia decomposition reaction with potential for application in large‐scale industrial processes. On the one hand, the requirements on the catalyst are quite demanding. Of central importance are the conditions for the primary reaction that have to be met by the catalyst. Likewise, the catalytic performance, i.e., an ideally quantitative conversion, and a high lifetime are critical as well as the consideration of requirements on the product properties in terms of pressure or by‐products for potential follow‐up processes, in this case synthesis gas applications. On the other hand, the evaluation of the multitude of literature studies poses difficulties due to significant varieties in catalytic testing protocols. Abstract : Ammonia decomposition over heterogeneous catalysts is one of the central pillars of the strategy to utilize ammonia as hydrogen vector in a greener energy economy and chemical industry. A suitable catalyst material is still to be identified, but with the recent surge in research on this topic, this challenge is likely to be tackled in the near future.